Pollen morphology and fruit anatomy of the enigmatic monotypic genus Dicranocarpus (Coreopsideae, Asteraceae) - Sánchez-Chávez, Erandi; Vovides, Andrew P.; Castro-Castro, Arturo; Sosa, Victoria (Phytotaxa, 2024)
Dicranocarpus is a monotypic genus endemic to the Chihuahuan Desert with atypical attributes among species of tribe Coreopsideae. Phylogenetic position of Dicranocarpus parviflorus has been controversial. A molecular phylogeny showed that the taxon was closely related to Dahlia; however, further analyses with a wider sampling of Dahlia, also including Hidalgoa, identified the genus in a more distant clade. The objective of this study is to gather anatomical attributes from the cypselae as well as palynological characters along with macromorphology to determine whether Dicranocarpus shares characters with these genera in Coreopsideae. Our results show that although the pollen of D. parviflorus does not possess attributes that distinguish it from the rest of the tribe Coreopsideae, they were useful to confirm its membership in the tribe. The cypselae anatomy identified that D. parviflorus has characters of taxonomic value that differentiate this species from the rest of the Coreopsideae. The three most significant novel characters in Dicranocarpus were in the outer mesocarp, consisting of tracheoidal-like cells forming irregular rows up to 250 μm in length, an aerenchyma in the middle mesocarp, and the lack of phytomelanin and calcium oxalate crystals. Furthermore, the results of the phytomelanin patterns in the studied taxa highlight the need for further anatomical studies of the cypselae to fully understand the evolution of phytomelanin deposition in the tribe Coreopsideae and even in the Heliantheae Alliance. Macromorphological, palynological and anatomical attributes of the cypsela in Dicranocarpus were not shared with Dahlia. Moreover, the sexual condition of the disc and ray florets shared with Hidalgoa has evolved independently in lineages of Asteraceae.